2018
DOI: 10.1002/nbm.3996
|View full text |Cite
|
Sign up to set email alerts
|

Waveguide effects and implications for cardiac magnetic resonance elastography: A finite element study

Abstract: Magnetic resonance elastography (MRE) is increasingly being applied to thin or small structures in which wave propagation is dominated by waveguide effects, which can substantially bias stiffness results with common processing approaches. The purpose of this work was to investigate the importance of such biases and artifacts on MRE inversion results in: (i) various idealized 2D and 3D geometries with one or more dimensions that are small relative to the shear wavelength; and (ii) a realistic cardiac geometry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In objects with at least one dimension smaller than about a wavelength (such as in the heart or within tumors), wave behavior depends on geometry as well as the inherent material properties, and such “waveguide effects” can dominate the wave propagation. Consequently, inversion approaches that do not account for this yield biased values 37,71 . This is particularly important in cardiac MRE with typical wall thicknesses around 10 mm.…”
Section: Nomenclature For Mrementioning
confidence: 99%
See 1 more Smart Citation
“…In objects with at least one dimension smaller than about a wavelength (such as in the heart or within tumors), wave behavior depends on geometry as well as the inherent material properties, and such “waveguide effects” can dominate the wave propagation. Consequently, inversion approaches that do not account for this yield biased values 37,71 . This is particularly important in cardiac MRE with typical wall thicknesses around 10 mm.…”
Section: Nomenclature For Mrementioning
confidence: 99%
“…54 Taking the curl of the displacement wave field in a homogeneous medium removes longitudinal contributions in theory, leaving behind a wave field that propagates at the true shear wave speed, corresponding to the intrinsic shear modulus. 37,71 However, there are practical difficulties: This requires full 3D data with good resolution in z, causes noise amplification, and low resolution may mean that spatial gradient operators may cross boundaries and yield incorrect results. Alternatively, some inversion approaches (eg, nonlinear inversion) may yield more accurate results near boundaries or in waveguide situations.…”
Section: Waveguide or Boundary Effectsmentioning
confidence: 99%
“…The displacement fields are then fed into the MRE reconstruction pipeline, which solves the inverse problem and retrieves the mechanical properties for comparison with groundtruth values. Simulations are generally based on analytical formulations [5,14,17,21] or finite element methods (FEM), either with custom-developed tools [22][23][24] or dedicated commercial softwares [20,[24][25][26][27][28][29][30]. Simulations are very useful to assess the error linked to reconstruction algorithms, however they do not suffice to reflect all potential limitations of an MRE experiment (transducer, B 0 and B 1 inhomogeneities, SNR, motion sensitivity, susceptibility issues, and heterogeneity of the material at very small scales).…”
Section: Introductionmentioning
confidence: 99%
“…In the Helmholtz equation, the medium is assumed to be infinite. For most soft tissues in which MRE has been performed (e.g., aorta, heart, and spinal cord), the media are bounded in which the propagating mechanical wave becomes complicated due to the relatively small dimensions and the geometry of the object 55 . Additionally, in bounded media, the equation of motion presented in Equation 2 will no longer hold and thus, new equations of motion that take geometry of the medium into account are needed.…”
Section: Mre Inversionmentioning
confidence: 99%
“…Promising results in different applications were observed. Manduca et al studied the waveguide effects in simulated cardiac MRE data using FEM and reported that inversion without curl processing resulted in biased stiffness values 55 . Moreover, it was observed that 3D inversion on curl-processed MRE data yielded more accurate stiffness estimation when compared to 2D inversion with curl processing, suggesting the importance of 3D MRE inversion.…”
Section: Mre Inversionmentioning
confidence: 99%